2023
DOI: 10.3847/1538-4357/acafe8
|View full text |Cite
|
Sign up to set email alerts
|

FEASTS: IGM Cooling Triggered by Tidal Interactions through the Diffuse H i Phase around NGC 4631

Abstract: We use the single-dish radio telescope Five-hundred meter Aperture Spherical Telescope (FAST) to map the H i in the tidally interacting NGC 4631 group with a resolution of 3.′24 (7 kpc), reaching a 5σ column density limit of 1017.9 cm−2 assuming a line width of 20 km s−1. Taking the existing interferometric H i image from the Hydrogen Accretion in LOcal GAlaxieS project of Westerbork Synthesis Radio Telescope as a reference, we are able to identify and characterize a significant excess of large-scale, low-den… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…To estimate the neutral ratio of hydrogen (N H I /N H ) of these H I features after 5 Gyr of photoionization, we take HVC 6 as an example, which has the lowest column density (2.04×10 18 cm −2 ). We fit the values of logU and N H I of HVC 6 in the model in Figure 24 of Wang et al (2023), and found that the resulting lower limit of N H I is 1.8%N H , which indicates 5 Gyr of photoionization does not ionize all H I. Another effect that needs to be considered is the effect of evaporation.…”
Section: Debris Of Tidal Features In a Merger?mentioning
confidence: 99%
“…To estimate the neutral ratio of hydrogen (N H I /N H ) of these H I features after 5 Gyr of photoionization, we take HVC 6 as an example, which has the lowest column density (2.04×10 18 cm −2 ). We fit the values of logU and N H I of HVC 6 in the model in Figure 24 of Wang et al (2023), and found that the resulting lower limit of N H I is 1.8%N H , which indicates 5 Gyr of photoionization does not ionize all H I. Another effect that needs to be considered is the effect of evaporation.…”
Section: Debris Of Tidal Features In a Merger?mentioning
confidence: 99%
“…For the time being, the most promising way to solve the problem is using large single-dish radio telescopes to fill in the "short spacings," in order to recover the large-scale missing H I (Stanimirovic 2002). Recent technical advances include Kurono et al (2009), Koda et al (2011), and Rau et al (2019), and recent scientific applications in this direction include Hess et al (2017), de Blok et al (2018, Richter et al (2018), Das et al (2020), Eibensteiner et al (2023), and Wang et al (2023). Most of these scientific studies confirm that interferometers tend to miss H I flux, though the exact amounts depend on source structures and telescope details.…”
Section: Introductionmentioning
confidence: 98%
“…But even in CGM and IGM, where the H I is insignificant in mass budget (Tumlinson et al 2017), its amount, distribution, and kinematics shed light on the complex gas physics there. Examples include the H I tidal structures possibly inducing gas cooling through turbulent mixing (Sparre et al 2022;Wang et al 2023), the predicted small H I cloudlets in the 10 7 K CGM of elliptical galaxies formed through thermal instabilities (Nelson et al 2020), the observed high-velocity H I clouds around the Milky Way (MW), marking the tip of the huge iceberg of the warm ionized gas being accreted onto the disk (Richter 2017), and the observed thick H I disk representing the interface of CGM condensing into the ISM (Marasco et al 2019). Detecting and characterizing the H I in different gaseous environments provide useful clues to galaxy evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The CGM is comprised of multiphase gases, dust (e.g., Whaley et al 2009), cosmic ray (CR), and magnetic field (e.g., Irwin et al 2012aIrwin et al , 2012b. The multiphase gases in the CGM include the hot gas (T  10 6 K) emitting X-rays (e.g., Li & Wang 2013a, 2013b, the transition-temperature gas (T ∼ 10 4-6 K; often called "warm-hot gas") most commonly traced by the rest-frame UV-absorption lines from high ions in the spectra of background active galactic nucleus (AGN; e.g., Chen & Mulchaey 2009;Tumlinson et al 2011;Stocke et al 2013), the T ∼ 10 3-4 K cool or warm gas (named differently in different studies, hereafter "warm gas" throughout this paper) seen in optical/UV emission lines (e.g., Collins et al 2000;Rossa & Dettmar 2003;Haffner et al 2009;Vargas et al 2019) or absorption lines from background AGN (e.g., Wakker & Savage 2009;Werk et al 2014), cold atomic gas often directly traced by the H I 21 cm line (e.g., Walter et al 2008;Heald et al 2011;Wang et al 2023), and molecular gas traced by many molecular lines typically in millimeter-wave (cold molecular gas, e.g., Young et al 1995;Leroy et al 2009) or IR (warm molecular gas, e.g., Veilleux et al 2009) ranges. This multiphase gaseous CGM serves as a reservoir from which the galaxy acquires baryons to continue star formation (SF; see the recent review Faucher-Giguère & Oh 2023).…”
Section: Introductionmentioning
confidence: 99%